OCCUPATIONAL STRESS AND FATIGUE WITH QUALITY OF LIFE IN THE TEXTILE INDUSTRY WORKERS - Ada', Yeremia Rante (Universitas Aisyah Pringsewu, 2024)
Occupational stress and fatigue in workers are problems that many workers experience. These two problems can not only have an impact on the organization but also on the quality of life of workers. This study aims to analyze the effect of work stress and fatigue on workers' quality of life. The study was conducted on 100 workers who work in a textile company. Bivariate statistical analysis using the Spearman test and multivariate analysis using linear regression with the help of SPSS version 25. The results showed that each work stress and fatigue significantly affected quality of life (p=0.00) with a Spearman correlation value for work stress of -0.351 and fatigue on quality of life of 0.444. Based on multivariate analysis, the Adjusted R Square value is 34%. The conclusion of this study is that the equation obtained is able to explain the quality of life by 34%, while the remaining 66% is explained by other variables that are not studied. This research is useful as a basis for future researchers to further examine other variables that affect the quality of life of textile workers.